Ritual and mourning in the digital era: between virtual technology and ethical controversies - Fusco, Roberta; Ciliberti, Rosagemma; Licata, Marta; Picozzi, Mario (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Digital technology has radically transformed how contemporary society perceives death and mourning. The concept of "digital death" and its implications have become a focal point of investigation. This article explores the intersection of digital technologies with traditional mourning rituals, analysing their influence on grief processing practices and providing insights into the complexities of managing grief in the digital age. Methods: Analysis of existing literature on emerging funeral technologies and the issues associated with new digital mourning practices. Results and discussion: Online mourning has opened new forms of commemoration and community building, offering support and interaction to those in need. However, it has also raised concerns and ethical challenges regarding the processing of loss, privacy, authenticity, and the commercialization of grief. Conclusions: It is crucial to promote the development of ethical guidelines for responsibly managing digital mourning. Raising awareness of the importance of a culture based on empathy and support, along with ensuring respect for the dignity and privacy of the deceased through the use of digital technologies, is crucial.